Influence of Onion Seedlings Planting Period and Age on Seeds Quality Indicators - Mirzasoypovich, Mirzasoliev Mirzaosimjon (International Journal on Integrated Education, 2023)
In the dry, hot climate of the Republic of Uzbekistan, the effect of planting onion seedlings of different ages on the soil free from the previous vegetables as a repeated crop for different periods on their growth and development is highlighted. It has been scientifically proven that when onion is grown from seedlings as a repeated crop, its planting dates and the age of seedlings differ from each other with more or less real leaves on each bush, as well as with the length, weight and diameter of the largest leaf, and the thickness or thinness of the false stem.